(untitled) (Architecture Image Studies, 2024)
Background. Pregnancy is a critical period that requires special attention to maternal health, particularly in terms of balanced nutrition and appropriate physical activity.Aim. This study aims to developing a web-based application called Trimestra which is specifically designed to help monitor nutrition and physical activity in pregnant women.Methods. The method designed in this study consists of data collection as the main idea for application design. The application has two main features and is designed based on user flow diagrams. The design is implemented through the creation of apps. The type of data used is quantitative data. This data is used as an initial survey for the design of mHealth apps. Data was taken from one of the midwifery practices in Surabaya with a scheme for organizing a pregnant women’s class attended by 13 participants.Results. The creation of Trimestra, a web-based platform, has effectively combined functionalities for tracking nutritional intake and physical activity throughout pregnancy. Developed using the Laravel framework, the system ensures efficient performance with smooth and responsive operation. Its interface was deliberately structured to be clear and accessible, enabling expectant mothers to conveniently monitor their daily diet as well as their physical exercise routines.Conclusions. The conclusion of this study is that the development of Trimestra can integrate balanced nutritional needs and encourage the creation of a healthy lifestyle by monitoring physical activity habits during pregnancy.